ANALISIS KOLEKTIBILITAS PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU BOGOR SUDIRMAN - Dinda Mutiara Rizki; Tubagus Rifqy Thantawi; Miftakhul Anwar (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
Abstract This research is motivated by the interest of researchers to explore the collectibility level of murabahah contract financing, especially at Bank Syariah Mandiri Bogor Sudirman Branch Office. The higher the murabahah contract financing at Bank Syariah Mandiri Bogor Sudirman Branch Office, it will result in an increase in murabahah receivables and affect the collectibility level of murabahah receivables every year. If there is non-performing financing (NPF), it will disrupt the collectibility level. Meanwhile, the murabahah contract is still the most popular contract in the financing process of Bank Syariah Mandiri Bogor Sudirman Branch Office. This research is qualitative. The analysis used in this research is descriptive qualitative. The results showed that the Bank Syariah Mandiri Bogor Sudirman Branch Office had complied with the provisions in the Bank Indonesia Regulations and the Financial Services Authority Regulations in terms of murabahah contract financing. The collectibility level of Bank Syariah Mandiri Bogor Sudirman Branch Office is always at a safe level with a non-performing financing (NPF) value below 5%, which is 3.51% at the time of this research.